Lezione di sguardi. Edoardo Detti fotografo - Lisini, Caterina (Studi e saggi, 2017)
This volume documents Edoardo Detti's photographic activity, perhaps a "side" aspect, yet a fascinating and essential one for understanding his personality and his work. Many things are known about Detti: the several works and projects created individually or during the long collaboration with Carlo Scarpa, the intense preservation of the Tuscan territory, the important political and cultural role as counsellor for urban planning of the Municipality of Florence and as president of the Italian National Urban Planning Institute. His peculiar poetic, which so deeply intertwines architectural sensitivity and intimate adherence to the measure and qualities of the Tuscan landscape, is less known and investigated, and it is an attitude of which this volume offers valuable interpretations. The selected images, all taken between the 1940s and 1950s with the famous 6x6 Rolleiflex, almost make up a parallel essay to his activity as a scholar and an architect, where a profound ability to read the settlements, resulting from a historical, structural and formal interpretation, manifests itself in a vision which is suspended between truthful documentation and poetic abstraction.